2014
DOI: 10.1088/2043-6262/5/4/045012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of molecular packing of zinc(II) porphyrins on the performance of field-effect transistors

Abstract: The charge-transport phenomena of organic conjugated materials have been intensively investigated because of the potential applications of these materials in electronics and optoelectronics. Among these applications, organic field-effect transistors (OFETs) fabricated from either thin films or well-defined single crystals as charge-transporting layers are the most promising electronic devices. In this work, the effect of molecular packing on the performance of OFETs is investigated through the fabrication and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Insights can be extracted from crystal structure data of Y3 (CCDC deposit no. 1912230), as shown in Figure in relation to typical interactions observed in porphyrin-based crystal structures. , As indicated in Figure a, the closest distance between two Y3 molecules is about 6.0 Å. This is much longer than between molecules characterized by π–π stacking, which usually show closest molecule–molecule distances between 3.4 and 3.6 Å .…”
Section: Resultsmentioning
confidence: 91%
“…Insights can be extracted from crystal structure data of Y3 (CCDC deposit no. 1912230), as shown in Figure in relation to typical interactions observed in porphyrin-based crystal structures. , As indicated in Figure a, the closest distance between two Y3 molecules is about 6.0 Å. This is much longer than between molecules characterized by π–π stacking, which usually show closest molecule–molecule distances between 3.4 and 3.6 Å .…”
Section: Resultsmentioning
confidence: 91%
“…The degree of molecular ordering and packing can impact various solid‐state properties of TPMs, including their charge transport properties [64,65] . DFT calculations revealed that the molecular geometry is significantly affected by the nature of the metal.…”
Section: Resultsmentioning
confidence: 99%
“…A much less-explored type of NFA is hybrid organic/inorganic coordination compounds, where the coordination with a main group element or transition metal provides an additional way to tune properties such as the molecular shape, crystallinity, and optoelectronic properties. Examples in the literature of coordination complexes specifically explored for organic photovoltaic applications include porphyrins and phthalocynanines, which are planar with a strong tendency to π-stack; boron dipyrromethenes (BODIPY) and boron azadipyrromethenes (aza-BODIPY), which are also planar conjugated molecules better known for their outstanding optical properties; and subphthalocyanines, which are umbrella-shaped conjugated molecules. , …”
Section: Introductionmentioning
confidence: 99%